The role of “Marketing and education Unit Park” in the development of parks in Putrajaya / Siti Mashita Ramli - Ramli, Siti Mashita (2010)
The issue in this report is to describe in detail the marketing program should be run by the "unit of marketing and educational park" to ensure their objectives meet the consumer awareness of garden products, services, parks and all parks programs, ensuring they can meet the requirements of customers and in the same time develop parks with the development of the country. With, the "unit of marketing and educational park" should ensure that marketing activities are planned to be arranged with more detailed and systematic. Promotion is the best way to disseminate information on the product and the service park is on offer at the park. Only through proper promotion, the message can be delivered and customers are aware of the park at Putrajaya. Thus “unit marketing and educational park" can review further steps should be taken to ensure customer satisfaction with products and services in the park has to offer. The main purpose of this report is to describe a much simpler role or responsibility "unit marketing and educational park" in ensuring that each promotion they run to gain customer awareness, and to meet customer needs and responsibilities "of marketing and education units of the park" in the aspect market parks in Putrajaya. To obtain accurate and valid information, methods of study have been taken to ensure that accurate information and fulfill the purpose of this report is to seek as much information and make conclusions from the results of the report. Research methodology of data collection methods, data serving and the questionnaire with the officers involved in the unit, and copyright resources.